The Synergy of the Development Planning Regulatory Framework with the National Legislation Program - Mumtaz Soraya Nasution (Pusbindiklatren Bappenas, 2023)
The preparation of regulatory framework in the Government Work Plan/National Medium Term Development Plan has not been fully aligned with the preparation of laws and regulations in the National Legislation Plan and or Program for Preparation of Government Regulations and Presidential Regulations. The main objective of this paper is to investigate the factors that hinder the coordination mechanism for drafting regulations and emphasize the importance of realizing synergies, focusing on achieving a coordinated approach in drafting regulations. This policy research paper adopted a normative juridical analysis and a qualitative approach based on empirical data. The findings suggest that the coordination mechanism for preparing regulations is not functioning optimally due to inhibiting factors. The inhibiting factors are the lack of awareness regarding of the importance in meeting the indicators for proposing a regulatory framework and the absence of regulations that mandated sector directorates and KL (ministries/agencies) to comply with these indicators. Also there was a lack of synergy in coordinating the drafting of regulations.